Concurrence of creditors over registrable movable property: analysis of the preference criteria established by article 1136 of the Civil Code and proposal for legislative reform - Rubio Alcántara, David (2024)
The current regime of concurrency of creditors of registrable movable assets has been the subject of numerous criticisms and comments. Therefore, this article will examine the treatment that this regime has received under the applicable legislation and current case law; as well as its relationship with the systems of transfer of ownership and the signs of cognizability of rights.The authors intend to identify the solutions offered by article 1136 of the Civil Code in this case in order to ask themselves and try to answer which would be the most appropriate regulation. To do so, they will use doctrine, case law and reform proposals.